Tingkat Kepercayaan Mahasiswa Akuntansi Terhadap Sistem Keamanan QRIS dalam Mencegah Kecurangan Transaksi - Linda; Cahyaning Dewi Handayani; Ayu Fitri Rosianie; Dheti Septiana; Nurul Maghfirotul Jannah (Jurnal Literasi Akuntansi, 2026)
Purpose: This study aims to examine the effect of perceived security on the trust of accounting students in using the Quick Response Code Indonesian Standard (QRIS) as a digital payment system, particularly in the context of fraud prevention. Method:This study employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to 100 accounting students selected using purposive sampling, with the criterion of having used QRIS at least once. The data were analyzed using the Statistical Package for the Social Sciences (SPSS), including validity and reliability tests, classical assumption tests, and simple linear regression analysis. Findings:The results indicate that perceived security has a positive and significant effect on user trust. This finding suggests that higher perceived security leads to greater trust in using QRIS. Furthermore, security plays an essential role in reducing fraud risks and enhancing user confidence in digital transactions. Novelty:The novelty of this study lies in the integration of perceived security, trust, and fraud prevention within a single research framework, focusing on accounting students who possess a deeper understanding of internal control and fraud risk. This study also extends technology acceptance theories by incorporating a security perspective in QRIS usage.